Pariwisata Terpadu Berbasis Mitigasi Bencana Tsunami Melalui Strategi Community Based Tourism di Gampong Nusa - Rizki, Muhammad; Nirzalin, Nirzalin; Maliati, Nulwita; Suadi, Suadi; Nasution, Abdullah Akhyar; Mursyidin, Mursyidin (Jurnal Community, 2024)
Nusa Tourism Village is a unique tourist village because this tourist village originates from the experience of the tsunami natural disaster. So that tourism practice is not only based on attractions and consumption but also contains tsunami disaster mitigation values. This research aims to analyze the integration of tourism and tsunami disaster mitigation in Gampong Nusa, Aceh Besar. The research location was carried out in the Nusa Tourism Village, Lhoknga District, Aceh Besar Regency. The research method used is qualitative with a case study approach. The research results show that there are three tourism programs that contain tsunami disaster mitigation values, namely homestays, handicrafts, and hiking, which not only provide tourism experiences but also provide education about disaster preparation and mitigation. Through folklore, personal experiences, and evacuation locations, this program combines cultural aspects, practical experiences, and learning in disaster mitigation. The concept of Community-Based Tourism (CBT) in Gampong Nusa not only emerged as a tourism strategy but also as a form of community solidarity in rebuilding villages after the tsunami disaster. The proposed new theory, namely the "integration model," highlights the active involvement of the community in supporting tourism and disaster mitigation programs, even without being directly involved in the formal tourism system.